Evolution of pluripotency: hijacking of an ancient network - Crowley, Darren Jerome (2018)
Pluripotency is conserved in the major trunk of Vertebrate evolution, but how the gene regulatory network (GRN) that governs it evolved is poorly understood. A central component of this network is the Homeodomain containing transcription factor Nanog. How Nanog evolved is not understood, as Nanog sequences have not been identified in invertebrate genomes. This study provides evidence of Nanog activity encoded in the homeodomain of the invertebrate Vent gene family. The Vent2 gene from Saccoglossus kowalevskii, a model hemichordate, successfully reprogrammed mammalian pre-iPS cells to pluripotency, as demonstrated by the activation of dormant pluripotency genes, and the ability to generate all three primary germ layers. A second property of invertebrate Vents was also characterised in the Vent gene found in Nematostella vectensis, a sea anemone and model for cnidarian development, expression of which was insufficient to activate the endogenous pluripotency network of pre-iPS cells, though it could induce the cells to a XEN-like state that demonstrated up regulation of extra-embryonic markers, and subsequently gained dependence on ERK signalling. A direct comparison between the Saccoglossus and Nematostella Vent homeodomains was used to provide insight into the step-wise changes that appear to have given rise to Nanog activity. Swapping the homeodomains from one CDS to another, to create hybrid molecules, I demonstrated that the respective reprogramming activities of these genes is conserved in the homeodomain. I then identified specific amino acid (AAs) differences in the homeodomains that conferred a Nanog-like capacity for reprogramming to the Nematostella gene. Identification of a Nematostella EsrrB ortholog, which demonstrated reprogramming activity in mammalian pre-iPS cells, suggests wider conservation of pluripotency factors. I therefore propose that an ancient GRN for pluripotent mesoderm evolved in vertebrates to form part of the ground state network.